Technostressors - a boon or bane? Towards an integrative conceptual model - Ramesh, Rofia; Ananthram, Subramaniam; Vijayalakshmi, V.; Sharma, Piyush (Emerald, 2021)
Purpose: This paper aims to highlight the positive and negative effects of technostressors on employee attitudes using psychological need satisfaction as an explanatory mechanism and mindfulness as an individual resource, thereby developing an integrative conceptual model.